Positive electrode and lithium secondary battery manufactured using the same

A dual-layer positive electrode design with specific binders and conductive materials addresses adhesive and flexibility issues in lithium iron phosphate batteries, improving adhesion and reducing resistance while maintaining high capacity.

JP2025500514AActive Publication Date: 2025-01-09LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024538446
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2023-10-26
Publication Date
2025-01-09
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

Lithium iron phosphate-based positive electrodes in lithium secondary batteries face issues with reduced adhesive strength and flexibility due to particle aggregation, leading to detachment during manufacturing or charging/discharging, which increases battery resistance and decreases capacity.

Method used

A positive electrode structure comprising two layers, each containing lithium iron phosphate, a fluorine-based binder, and hydrogenated nitrile butadiene rubber with specific molecular weights and ratios, enhances adhesive strength and flexibility by improving interfacial adhesion without additional bonding layers.

Benefits of technology

The dual-layer structure significantly improves cathode adhesion and flexibility, reducing battery resistance and enhancing capacity and output characteristics, particularly in high-loading electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500514000001
    Figure 2025500514000001
  • Figure 2025500514000002
    Figure 2025500514000002
  • Figure 2025500514000003
    Figure 2025500514000003
Patent Text Reader

Abstract

According to the present invention, there is provided a positive electrode including a current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate, a fluorine-based binder, a first hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, a second hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more, and a conductive material, and a ratio (P2 / P1) of a weight P1 of fluorine contained in the first positive electrode active material layer to a weight P2 of fluorine contained in the second positive electrode active material layer is 1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2022-0139726 filed on October 26, 2022 and Korean Patent Application No. 10-2023-0143944 filed on October 25, 2023.

[0002] The present invention relates to a positive electrode and a lithium secondary battery manufactured using the same, and more particularly to a high-loading positive electrode having excellent flexibility and adhesive strength and a lithium secondary battery including the same. [Background technology]

[0003] As technological development and demand for electric vehicles and energy storage systems (ESS) increases, the demand for batteries as energy sources is rapidly increasing, and various researches are being conducted on batteries that can meet various requirements. In particular, active researches are being conducted on lithium secondary batteries that have high energy density as a power source for such devices and have excellent life and cycle characteristics.

[0004] Lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate (LFP), etc. are used as positive electrode active materials for lithium secondary batteries.

[0005] Lithium iron phosphate is low-cost because it contains iron, which is an abundant and low-cost material. In addition, lithium iron phosphate has low toxicity, so its use can reduce environmental pollution. Furthermore, because lithium iron phosphate has an olivine structure, the active material structure can be stably maintained at high temperatures compared to lithium transition metal oxides with a layered structure. This provides the battery with excellent high-temperature stability and high-temperature life characteristics.

[0006] However, lithium iron phosphate has a problem of low electrical conductivity due to reduced lithium mobility compared to lithium transition metal oxides such as lithium nickel cobalt manganese oxide. Therefore, in the past, lithium iron phosphate with a small average particle size was used to form a short lithium migration path, and the surface of the lithium iron phosphate was coated with carbon to improve electrical conductivity, and an excessive amount of conductive material was used.

[0007] However, as the size of lithium iron phosphate particles decreases, the specific surface area increases, and the lithium iron phosphate with a carbon-coated surface has reduced wettability with a solvent. As a result, lithium iron phosphate particles severely aggregate, the stability and coating processability of the positive electrode slurry decrease, and the lithium iron phosphate and binder do not mix effectively, resulting in a decrease in the adhesive strength between the positive electrode current collector and the positive electrode active material layer in the manufactured positive electrode (hereinafter, positive electrode adhesive strength). This phenomenon can be exacerbated in high loading positive electrodes.

[0008] If the adhesive strength of the positive electrode is reduced, the positive electrode active material layer may be detached during the manufacture of the electrode or during charging and discharging, which may lead to an increase in battery resistance and a decrease in the capacity of the secondary battery.

[0009] Korean Patent Publication No. 10-2020-0008066 discloses a binder composition for secondary battery electrodes, which contains an alkylene structural unit and a nitrile group-containing monomer unit in order to disperse a conductive material well, and also contains a copolymer having a predetermined Mooney viscosity. However, when the binder composition is directly applied to a positive electrode using lithium iron phosphate as the positive electrode active material, the binder composition is not satisfactory in terms of improving adhesion and flexibility.

[0010] Therefore, there is a need for a technique to improve the adhesion and flexibility of high loading positive electrodes, including lithium iron phosphate. Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention aims to provide a positive electrode and a lithium secondary battery in which, in a positive electrode containing lithium iron phosphate as a positive electrode active material, the adhesive strength between a positive electrode current collector and a positive electrode active material layer is improved, and the flexibility of the positive electrode is improved, thereby preventing electrode detachment, reducing battery resistance, and improving battery capacity. [Means for solving the problem]

[0012] According to one embodiment of the present invention, a positive electrode is provided, the positive electrode including a current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer, the first positive electrode active material layer and the second positive electrode active material layer each including lithium iron phosphate, a fluorine-based binder, a rubber-based binder, and a conductive material, the rubber-based binder including a first hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol and a second hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more, and a ratio (P2 / P1) of a weight P1 of fluorine contained in the first positive electrode active material layer to a weight P2 of fluorine contained in the second positive electrode active material layer is 1 or less.

[0013] In one embodiment, a ratio (P2 / P1) of a weight P2 of fluorine contained in the second positive electrode active material layer to a weight P1 of fluorine contained in the first positive electrode active material layer is 0.5-1.

[0014] In one embodiment, the first positive electrode active material layer contains 0.9 wt % or less of the second hydrogenated nitrile butadiene rubber based on the weight of the first positive electrode active material layer.

[0015] In one embodiment, a weight ratio of the fluorine-based binder and the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer is 90:10 to 75:25; The weight ratio of the fluorine-based binder to the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer is 80:20 to 60:40.

[0016] In one embodiment, the first positive electrode active material layer has a weight ratio of about 1: 93.5% by weight to 97.99% by weight of the lithium iron phosphate, 1.5% by weight to 3.0% by weight of the fluorine-based binder, 0.01% by weight to 0.7% by weight of the first hydrogenated nitrile butadiene rubber, 0.2% by weight to 0.8% by weight of the second hydrogenated nitrile butadiene rubber, The conductive material is contained in an amount of 0.3% by weight to 2.0% by weight.

[0017] In one embodiment, the second positive electrode active material layer has a weight ratio of, based on the weight of the second positive electrode active material layer, 94.2% by weight to 98.49% by weight of the lithium iron phosphate, 0.9% by weight to 2.2% by weight of the fluorine-based binder, 0.01% by weight to 0.7% by weight of the first hydrogenated nitrile butadiene rubber, 0.3% by weight to 0.9% by weight of the second hydrogenated nitrile butadiene rubber, The conductive material is contained in an amount of 0.3% by weight to 2.0% by weight.

[0018] In one embodiment, the weight average molecular weight (Mw) of the second hydrogenated nitrile butadiene rubber is 150,000 g / mol to 1,000,000 g / mol.

[0019] In one embodiment, the fluorine-based binder contained in the first positive electrode active material layer and the fluorine-based binder contained in the second positive electrode active material layer are the same compound.

[0020] In one embodiment, the ratio (=H2 / H1) of the weight % (H1) of the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer to the weight % (H2) of the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer is 1 to 3.

[0021] In one embodiment, the lithium iron phosphate is a compound represented by the following Formula 1:

[0022] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b

[0023] (In the above chemical formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.)

[0024] In one embodiment, the conductive material is carbon nanotubes.

[0025] In one embodiment, the ratio (C2 / C1) of the weight % C2 of the conductive material contained in the second positive electrode active material layer to the weight % C1 of the conductive material contained in the first positive electrode active material layer is 0.5-2.

[0026] In one embodiment, the total loading amount of the first positive electrode active material layer and the second positive electrode active material layer is 400 mg / 25 cm 2 ~700mg / 25cm 2 is in the range.

[0027] In one embodiment, the positive electrode has a positive electrode adhesion strength of 22 gf / 20 mm or more, as measured in an adhesion strength test in which the first positive electrode active material layer is peeled off at 90° from an aluminum thin film.

[0028] In one embodiment of the positive electrode, cracks occur with a measuring rod of 5 phi or less during a flexibility test in which a cross section of the positive electrode is lifted after contacting the positive electrode active material layer with a measuring rod of phi.

[0029] According to another embodiment of the present invention, there is provided a lithium secondary battery including the above positive electrode. Effect of the Invention

[0030] The positive electrode according to the present invention is composed of a plurality of layers, each of which contains a fluorine-based binder, a first hydrogenated nitrile-butadiene rubber having a weight average molecular weight in a different range, and a second hydrogenated nitrile-butadiene rubber. The ratio (P2 / P1) of the weight P1 of fluorine contained in the first positive electrode active material layer to the weight P2 of fluorine contained in the second positive electrode active material layer is controlled to 1 or less, so that the positive electrode can have excellent positive electrode adhesion and flexibility even with a small binder content compared to a conventional single-layer positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The advantages and features of the present invention, and the methods for achieving them, will become clear from the detailed description of the embodiments below in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms, and the present embodiments are provided solely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is only defined by the scope of the claims. The same reference numerals refer to the same elements throughout the specification.

[0032] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used as commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless otherwise clearly defined.

[0033] The terms used in this specification are for the purpose of describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the context. The words "comprises" and / or "comprising" used in the specification do not exclude the presence or addition of one or more other components other than the components mentioned.

[0034] In this specification, when a part includes a certain component, this does not mean that it excludes other components, and it means that it may further include other components, unless specifically stated to the contrary.

[0035] In this specification, the phrase "A and / or B" means A or B, or A and B.

[0036] In this specification, "%" means % by weight unless expressly indicated otherwise.

[0037] In this specification, D 50 D means the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured, for example, by using a laser diffraction method. The laser diffraction method generally enables measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.

[0038] In this specification, the "specific surface area" is measured by the BET method, and specifically, it can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.

[0039] In the present specification, the term "weight average molecular weight (Mw)" refers to a value converted to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value converted from a value measured under the following conditions using GPC, and standard polystyrene from an Agilent system was used to create a calibration curve.

[0040] <Measurement conditions> Measuring instrument: Agilent GPC (Agilent 1200 series, USA) Column: PL Mixed B 2 pieces connected Column temperature: 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0mL / min Concentration: ~1mg / mL (100μL injection)

[0041] The positive electrode adhesive strength in this specification can be measured by the following method. A positive electrode cut to a length of 150 mm and a width of 20 mm is prepared, and the positive electrode active material layer is made to face a slide glass of a length of 75 mm and a width of 25 mm, and the positive electrode is attached to the slide glass in the longitudinal direction using double-sided tape. That is, the slide glass is attached to an area corresponding to half of the longitudinal direction of the positive electrode. Then, a roller is rolled 10 times so that the double-sided tape is evenly attached to prepare an evaluation sample. Next, the slide glass part of the evaluation sample is fixed to the sample stage of a Universal Testing Machine (UTM) (LS5, AMETEK), and the half of the positive electrode to which the slide glass is not attached is connected to a load cell equipped with the UTM. The load cell is moved up to 50 mm at a speed of 100 mm / min by applying a force of 90° and measuring the load applied to the load cell. At this time, the average value of the load measured in the 20 mm to 40 mm section of the running section is calculated. This is repeated a total of five times, and the average value is evaluated as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0042] The flexibility of the positive electrode in this specification can be measured by the following method. A measuring rod with a diameter of 600 mg / 25 cm 2 A positive electrode with a loading of 10 ...

[0043] The present invention will be specifically described below.

[0044] <Positive electrode> The positive electrode for a lithium secondary battery according to the present invention will now be described.

[0045] A positive electrode according to an embodiment of the present invention is a positive electrode including a current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate, a fluorine-based binder, a rubber-based binder, and a conductive material, and the rubber-based binder includes a first hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol and a second hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more, and a ratio (P2 / P1) of a weight P1 of fluorine contained in the first positive electrode active material layer to a weight P2 of fluorine contained in the second positive electrode active material layer is 1 or less.

[0046] Lithium iron phosphate has a lower lithium mobility and lower electrical conductivity than lithium transition metal oxides such as lithium nickel cobalt manganese oxide, so lithium iron phosphate with a small average particle size is mainly used as a positive electrode active material. However, when the size of the lithium iron phosphate particles is small, the specific surface area increases, which causes severe particle aggregation and the lithium iron phosphate and binder are not effectively mixed, resulting in a decrease in the positive electrode adhesive strength. As a result, there is a problem that the positive electrode active material layer is detached during electrode manufacturing or charging and discharging, increasing the battery resistance and reducing the capacity of the secondary battery.

[0047] As a result of extensive research to solve such problems, the inventors have discovered that when a positive electrode active material layer is composed of two layers, the binders contained in each layer include a fluorine-based binder, the first hydrogenated nitrile butadiene rubber, and the second hydrogenated nitrile butadiene rubber, and the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer is 1 or less, the interfacial adhesion between the current collector and the first positive electrode active material layer is dramatically increased, the flexibility of the entire positive electrode active material layer is improved, and the resistance of the positive electrode is reduced, thereby completing the present invention.

[0048] The positive electrode according to one embodiment of the present invention has a structure in which the positive electrode active material layer is in direct contact with the positive electrode current collector, and may not include a separate layer for improving adhesion between the positive electrode active material layer and the positive electrode current collector due to excellent interfacial adhesion between the positive electrode active material layer and the positive electrode current collector. That is, the positive electrode according to one embodiment of the present invention may exhibit excellent interfacial adhesion even without including a separate layer such as a binder layer, adhesive layer, bonding layer, or primer coating layer that may be interposed between the positive electrode current collector and the positive electrode active material layer for improving adhesion.

[0049] The positive electrode of the present invention will now be described in detail.

[0050] A positive electrode according to one embodiment of the present invention may include a positive electrode active material layer. Specifically, a positive electrode according to the present invention may include a positive electrode current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer. In this case, the first positive electrode active material layer and the second positive electrode active material layer may be formed on one or both sides of the current collector.

[0051] The positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector may be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.

[0052] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and may have fine irregularities on its surface to enhance adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0053] The first and second positive electrode active material layers may each include a positive electrode active material. Additionally, the first and second positive electrode active material layers may further include a conductive material, a binder, and a dispersant, if necessary, in addition to the positive electrode active material.

[0054] Hereinafter, each component contained in the positive electrode active material layer will be specifically described.

[0055] (1) Positive electrode active material The present invention includes lithium iron phosphate as a positive electrode active material. Specifically, the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate as a positive electrode active material. Since lithium iron phosphate has an olivine structure, the active material structure is more stably maintained at high temperatures than lithium transition metal oxides having a layered structure. As a result, when lithium iron phosphate is used as a positive electrode active material, the high temperature stability and high temperature life characteristics of the positive electrode are significantly improved, thereby reducing the risk of fire of a lithium secondary battery including the positive electrode.

[0056] The lithium iron phosphate may be a compound represented by the following formula 1:

[0057] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b

[0058] (In the above chemical formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.)

[0059] For example, the lithium iron phosphate can be LiFePO4.

[0060] The lithium iron phosphate may be in the form of secondary particles formed by agglomeration of primary particles, and preferably has a monolithic structure consisting of primary particles.

[0061] In the present invention, the term "monolith structure" refers to a structure in which particles are not morphologically aggregated and exist in independent phases. A particle structure that is contrasted with this monolith structure is a structure in which small particles ("primary particles") are physically and / or chemically aggregated to form relatively large particles ("secondary particles").

[0062] When lithium iron phosphate has a monolithic structure made of primary particles, the possibility of the lithium iron phosphate particles cracking during rolling is small compared to when it is made of secondary particles, which is preferable because capacity loss due to detachment of the cracked particles is small. Also, when lithium iron phosphate is made of monolithic primary particles, it can be said to be preferable in terms of interfacial adhesion between the positive electrode current collector and the positive electrode active material layer because it can mitigate the migration of the binder during the drying process of the positive electrode slurry.

[0063] The lithium iron phosphate may include a carbon coating layer on the surface. When a carbon coating layer is formed on the surface of the lithium iron phosphate, the electrical conductivity is improved, and the resistance characteristics of the positive electrode may be improved.

[0064] The carbon coating layer may be formed using at least one raw material selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol polymers, ethylene and ethylene oxide block copolymers, vinyl resins, cellulose resins, phenol resins, pitch resins, and tar resins. Specifically, the carbon coating layer may be formed by mixing the raw material with the lithium iron phosphate and then heat treating the mixture.

[0065] Average particle size of lithium iron phosphate D 50 The average particle diameter D of the positive electrode active material may be 0.8 μm to 20.0 μm, specifically 0.9 μm to 10.0 μm, and more specifically 0.9 μm to 3.0 μm. 50When satisfies the above range, the mobility of lithium in the lithium iron phosphate is improved, and the charge / discharge characteristics of the battery can be improved.

[0066] The BET specific surface area of ​​lithium iron phosphate is 5m 2 / g~20m 2 / g, specifically 7m 2 / g~18m 2 / g, more specifically 9m 2 / g~16m 2 / g. This range corresponds to a lower value compared to typical lithium iron phosphate. When this range is satisfied, aggregation of the lithium iron phosphate can be effectively suppressed even in a positive electrode slurry composition having a relatively low content of a dispersant.

[0067] In one embodiment, the first positive electrode active material layer may contain 93.5% to 97.99% by weight, specifically 94% to 97.5% by weight, and more specifically 94.4% to 97% by weight of the lithium iron phosphate, based on the weight of the first positive electrode active material layer.

[0068] In one embodiment, the second positive electrode active material layer may contain the lithium iron phosphate in an amount of 94.2 wt % to 98.49 wt %, specifically 94.5 wt % to 98 wt %, and more specifically 95 wt % to 97.5 wt %, based on the weight of the second positive electrode active material layer.

[0069] When the content of the lithium iron phosphate satisfies the above range, a sufficient positive electrode energy density is ensured, and the battery capacity of the positive electrode can be improved.

[0070] (2) Binder The first positive electrode active material layer and the second positive electrode active material layer of the present invention each contain, as a binder, both a fluorine-based binder and a rubber-based binder, and the rubber-based binder contains a first hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, and a second hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more.

[0071] In this case, the content (wt%) of the fluorine-based binder contained in the first lower positive electrode active material layer is equal to or greater than the content (wt%) of the fluorine-based binder contained in the second upper positive electrode active material layer, and the ratio (P2 / P1) of the weight P2 of the fluorine contained in the second positive electrode active material layer to the weight P1 of the fluorine contained in the first positive electrode active material layer is 1 or less, preferably 0.5 to 1, and more preferably 0.52 to 0.95. If the ratio (P2 / P1) of P2 to P1 exceeds 1, it is not preferable from the viewpoint of adhesive strength.

[0072] The weight P1 of fluorine contained in the first positive electrode active material layer and the weight P2 of fluorine contained in the second positive electrode active material layer satisfy the above ratio range due to the difference in the content of the fluorine-based binder contained in the first positive electrode active material layer and the second positive electrode active material layer, respectively.

[0073] That is, although the fluorine-based binder contains elemental fluorine, the lithium iron phosphate, the first hydrogenated nitrile butadiene rubber, the second hydrogenated nitrile butadiene rubber and the conductive material which constitute the positive electrode of the present invention do not contain a fluorine component, and therefore the weight of fluorine contained in each of the first positive electrode active material layer and the second positive electrode active material layer is proportional to the content (weight) of the fluorine-based binder contained in each of the first positive electrode active material layer and the second positive electrode active material layer.

[0074] The fluorine-based binder contained in the first positive electrode active material layer and the fluorine-based binder contained in the second positive electrode active material layer may be the same compound having the same weight average molecular weight and chemical formula.

[0075] The fluorine-based binder includes polyvinylidene fluoride (PVDF)-based polymers containing vinylidene fluoride (VDF) as a monomer. Specific examples of the PVDF-based polymers include PVDF homopolymer, PVDF-HFP (Poly(vinylidene fluoride-co-hexafluoropropylene)), PVDF-CTFE (Poly(vinylidene fluoride-co-chlorotrifluoroethylene)), PVDF-TFE (Poly(vinylidene tetrafluoroethylene)), and PVDF-TrFE (Poly(vinylidene trifluoroethylene)).

[0076] In one specific example, the fluorine-based binder may be included in the first positive electrode active material layer in an amount of 1.5 wt% to 3.0 wt%, preferably 1.6 wt% to 2.7 wt%, and more preferably 1.7 wt% to 2.5 wt%, based on the weight of the first positive electrode active material layer, and the fluorine-based binder may be included in the second positive electrode active material layer in an amount of 0.9 wt% to 2.2 wt%, preferably 1.0 wt% to 2.1 wt%, and more preferably 1.2 wt% to 2.0 wt%, based on the weight of the second positive electrode active material layer.

[0077] In addition, in the entire positive electrode active material layer including the first positive electrode active material layer and the second positive electrode active material layer, the fluorine-based binder may be contained in an amount of 1.2 wt % to 2.6 wt %, preferably 1.4 wt % to 2.4 wt %, and more preferably 1.6 wt % to 2.2 wt %.

[0078] When the content of the fluorine-based binder is within the above range, it can be said that the viscosity and coating stability of the positive electrode slurry are excellent, while the adhesive strength and flexibility of the positive electrode are doubled.

[0079] The weight average molecular weight (Mw) of the fluorine-based binder may be 300,000 to 2,000,000, preferably 400,000 to 1,500,000, and most preferably 500,000 to 1,300,000. When the weight average molecular weight of the fluorine-based binder satisfies the above numerical range, the viscosity of the positive electrode slurry is likely to be in a preferred range, and the positive electrode adhesive strength can be maximized even with a small content range.

[0080] Fluorine-based binders are commonly used as electrode binders due to their excellent adhesive strength and chemical stability against electrolytes. However, due to their crystal structure, if the amount of fluorine-based binder is excessive, it can have a negative effect on the flexibility of the positive electrode. On the other hand, the higher the binder content, the higher the adhesive strength of the positive electrode, so improving the adhesive strength and flexibility of the positive electrode was a challenge that was difficult to achieve by simply adjusting the binder content. In addition, when the loading amount of the positive electrode active material layer was 600 mg / 25 cm, 2 The high-loading positive electrode described above tends to have inferior flexibility compared to a low-loading positive electrode having the same binder content and a smaller loading amount, so improving the flexibility as well as the adhesive strength in a high-loading positive electrode has been a difficult technical challenge.

[0081] Therefore, the positive electrode according to the present invention contains a rubber-based binder in addition to the fluorine-based binder, and the rubber-based binder contains a first hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol and a second hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more.

[0082] The first hydrogenated nitrile butadiene rubber not only improves the adhesive strength and flexibility of the positive electrode, but also improves the dispersibility of the positive electrode slurry to suppress the aggregation of the conductive material and the positive electrode active material. The inventors of the present invention have discovered that when the positive electrode contains only the first hydrogenated nitrile butadiene rubber as a rubber-based binder, the adhesive strength and flexibility of the positive electrode cannot be further improved at a certain content or more, but when the positive electrode contains the second hydrogenated nitrile butadiene rubber together with the first hydrogenated nitrile butadiene rubber, the flexibility and adhesive strength of the positive electrode are dramatically increased, leading to the present invention. As a result, the positive electrode according to the present invention is excellent in both flexibility and adhesive strength, and when the loading amount of the positive electrode increases, the improved flexibility provides excellent rolling performance. In addition, the improved flexibility contributes to preventing the positive electrode active material layer from being detached when a physical impact is applied to the outside of the positive electrode.

[0083] The first hydrogenated nitrile butadiene rubber and the second hydrogenated nitrile butadiene rubber (HNBR) are obtained by subjecting each nitrile butadiene rubber (NBR) to a hydrogenation reaction, and thereby converting the double bonds originally contained in the nitrile butadiene rubber (NBR) into single bonds.

[0084] The hydrogenated nitrile butadiene rubber may have a repeating unit content derived from acrylonitrile (AN) of 20% by weight to 50% by weight, more preferably 25% by weight to 45% by weight, and most preferably 30% by weight to 40% by weight, based on the total weight.

[0085] The rubber-based binder of the present invention contains a first hydrogenated nitrile butadiene rubber and a second hydrogenated nitrile butadiene rubber having different weight average molecular weight ranges.

[0086] The first hydrogenated nitrile butadiene rubber may have a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, preferably 10,000 g / mol to 80,000 g / mol, and more preferably 10,000 g / mol to 50,000 g / mol, and improves the solvent wetting and dispersibility of lithium iron phosphate particles and inhibits particle aggregation of lithium iron phosphate.

[0087] In addition, the first hydrogenated nitrile butadiene rubber inhibits the agglomeration of the conductive material, improves the positive electrode conductive network, and even if the conductive material aggregates, it aggregates in a spherical shape rather than a linear shape, thereby minimizing the specific surface area of ​​the aggregated conductive material compared to when the conductive material aggregates in a linear shape. As a result, the surface area of ​​the positive electrode active material adjacent to the aggregated conductive material that cannot participate in the lithium insertion / extraction reaction is minimized, thereby reducing the discharge resistance of the lithium secondary battery.

[0088] The weight average molecular weight (Mw) of the second hydrogenated nitrile butadiene rubber is 130,000 g / mol or more, preferably 150,000 g / mol to 1,000,000 g / mol, more preferably 200,000 g / mol to 500,000 g / mol. When the weight average molecular weight (Mw) of the second hydrogenated nitrile butadiene rubber is 130,000 g / mol or more, the adhesive strength and flexibility of the positive electrode active material layer can be improved, and the rolling density of the positive electrode can be increased, and the higher the rolling density, the lower the positive electrode resistance can be obtained.

[0089] In one specific example, the first hydrogenated nitrile-butadiene rubber may be contained in the first positive electrode active material layer in an amount of 0.01% by weight to 0.7% by weight, preferably 0.05% by weight to 0.6% by weight, more preferably 0.1% by weight to 0.5% by weight. The first hydrogenated nitrile-butadiene rubber may also be contained in the second positive electrode active material layer in the above-mentioned range.

[0090] When the content of the first hydrogenated nitrile butadiene rubber is within the above range, the positive electrode slurry can have a viscosity suitable for coating, and the lithium iron phosphate, conductive material, and binder in the positive electrode slurry can be well dispersed.

[0091] In one specific example, the second hydrogenated nitrile butadiene rubber is contained in the first positive electrode active material layer at 0.9 wt% or less, preferably 0.2 wt% to 0.8 wt%, more preferably 0.3 wt% to 0.6 wt%, based on the weight of the first positive electrode active material layer. Also, the second hydrogenated nitrile butadiene rubber is contained in the second positive electrode active material layer at 0.9 wt% or less, preferably 0.3 wt% to 0.9 wt%, more preferably 0.5 wt% to 0.8 wt%, based on the weight of the second positive electrode active material layer.

[0092] In addition, in the entire positive electrode active material layer including the first positive electrode active material layer and the second positive electrode active material layer, the total weight percent of the second hydrogenated nitrile butadiene rubber may be 0.9 weight percent or less, preferably 0.25 weight percent to 0.85 weight percent, more preferably 0.35 weight percent to 0.75 weight percent, and most preferably 0.4 weight percent to 0.65 weight percent.

[0093] If the second hydrogenated nitrile butadiene rubber is included in an excessive amount outside the above range, it exerts a synergistic effect with the fluorine-based binder, dramatically increasing the viscosity of the positive electrode slurry and causing poor coating properties. As a result, it may be impossible to manufacture the positive electrode. Also, if the second hydrogenated nitrile butadiene rubber is included in an excessively small amount outside the above range, the effect of improving the flexibility and adhesive strength of the positive electrode may be small. Therefore, it is preferable that the second hydrogenated nitrile butadiene rubber is included in the above range.

[0094] In one specific example, the ratio (=H2 / H1) of the weight % (H2) of the second hydrogenated nitrile-butadiene rubber contained in the second positive electrode active material layer to the weight % (H1) of the second hydrogenated nitrile-butadiene rubber contained in the first positive electrode active material layer may be 1 to 3, preferably 1 to 2.9, and more preferably 1.1 to 2.8. Here, the weight % may be the weight ratio of the second hydrogenated nitrile-butadiene rubber contained in the first positive electrode active material layer based on 100 parts by weight of the first positive electrode active material layer, or the weight ratio of the second hydrogenated nitrile-butadiene rubber contained in the second positive electrode active material layer based on 100 parts by weight of the second positive electrode active material layer.

[0095] If the ratio (H2 / H1) of the weight % (H1) of the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer to the weight % (H2) of the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer exceeds 3, the second hydrogenated nitrile butadiene rubber is contained in the second positive electrode active material layer in an excessively large amount, which is undesirable because the viscosity of the slurry for the second positive electrode active material layer increases and the coating performance may decrease. Conversely, if it is less than 1, the second hydrogenated nitrile butadiene rubber is contained in the second positive electrode active material layer in an excessively small amount, which is undesirable because the flexibility of the entire positive electrode may decrease.

[0096] The first hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer and the first hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer may be the same compound, and may have the same weight average molecular weight and chemical formula.

[0097] In addition, the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer and the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer may be the same compound, and may have the same weight average molecular weight and chemical formula.

[0098] In one specific example, the weight ratio of the fluorine-based binder to the second hydrogenated nitrile-butadiene rubber contained in the first positive electrode active material layer may be 90:10 to 75:25, preferably 8:1 to 4:1, and more preferably 7:1 to 4:1. When the weight ratio of the fluorine-based binder to the second hydrogenated nitrile-butadiene rubber contained in the first positive electrode active material layer satisfies the above numerical range, it can be said that the coating stability of the slurry is excellent and the interfacial adhesion between the current collector and the first positive electrode active material layer is excellent.

[0099] The weight ratio of the fluorine-based binder to the second hydrogenated nitrile-butadiene rubber contained in the second positive electrode active material layer may be 80:20 to 60:40, and preferably 75:25 to 60:40. When the weight ratio of the fluorine-based binder to the second hydrogenated nitrile-butadiene rubber contained in the second positive electrode active material layer satisfies the above numerical range, it can be said that the coating stability of the slurry is excellent and the flexibility of the positive electrode is excellent.

[0100] In addition, the total amount of the fluorine-based binder, the first hydrogenated nitrile butadiene rubber, and the second hydrogenated nitrile butadiene rubber contained in the first and second positive electrode active material layers may be 1.8% by weight to 3.3% by weight based on the entire positive electrode active material layer.

[0101] (3) Conductive material The first positive electrode active material layer and the second positive electrode active material layer of the present invention each contain a conductive material.

[0102] The conductive material is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and may be, for example, graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. Specific examples of commercially available conductive materials include acetylene black series products (Chevron Chemical Company, Denka Singapore Private Limited, Gulf Oil Company products, etc.), Ketjenblack, EC series (Armak Company products), Vulcan XC-72 (Cabot Company products), and Super P (Timcal product). Preferably, the conductive material may be carbon nanotubes. A conductive network of carbon nanotubes can alleviate the binder lift-off phenomenon during the drying process of the positive electrode slurry, and is therefore preferable as the conductive material contained in the positive electrode of the present invention.

[0103] In one specific example, the first positive electrode active material layer may contain the conductive material in an amount of 0.3 wt% to 2.0 wt%, specifically 0.6 wt% to 1.5 wt%, more specifically 0.8 wt% to 1.3 wt%, based on the weight of the first positive electrode active material layer. Also, the second positive electrode active material layer may contain the conductive material in an amount of 0.3 wt% to 2.0 wt%, specifically 0.6 wt% to 1.5 wt%, more specifically 0.8 wt% to 1.3 wt%, based on the weight of the second positive electrode active material layer. When the content of the conductive material in the first positive electrode active material layer and the second positive electrode active material layer satisfies the above range, the positive electrode conductive network is ensured, thereby improving the electrical conductivity of the positive electrode.

[0104] In a preferred embodiment of the present invention, the ratio (C2 / C1) of the weight % C2 of the conductive material contained in the second positive electrode active material layer to the weight % C1 of the conductive material contained in the first positive electrode active material layer may be 0.1 to 3, preferably 0.5 to 2, and more preferably 0.5 to 1. When the weight % of the conductive material contained in the first positive electrode active material layer in contact with the current collector is the same as or greater than the weight % of the conductive material contained in the second positive electrode active material layer, the floating phenomenon of the conductive material in the first positive electrode active material layer is alleviated, thereby providing an effect of further improving the interfacial adhesion between the first positive electrode active material layer and the current collector.

[0105] The positive electrode may be manufactured according to a typical positive electrode manufacturing method, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by preparing a positive electrode slurry for the first positive electrode active material layer and a positive electrode slurry for the second positive electrode active material layer, each containing the positive electrode active material, conductive material, and binder, applying the slurry to the positive electrode current collector using a dual slot die, and then drying and rolling the slurry.

[0106] Alternatively, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0107] The positive electrode slurry for the first positive electrode active material layer and the positive electrode slurry for the second positive electrode active material layer according to an embodiment of the present invention may each have a viscosity of 5,000 cps to 25,000 cps, specifically 6,000 cps to 24,000 cps, more specifically 6,500 cps to 23,000 cps, measured at 25° C. and a shear rate of 2.5 / s. The positive electrode slurry having a viscosity value within the above range may have excellent storage stability and coating processability.

[0108] The positive electrode according to one embodiment of the present invention is a high-loading positive electrode, and the total loading amount of the first positive electrode active material layer and the second positive electrode active material layer is 400 mg / 25 cm. 2 ~700mg / 25cm2 For details, see 500mg / 25cm 2 ~650mg / 25cm 2 , more specifically 550mg / 25cm 2 ~650mg / 25cm 2 Here, the above loading amount is a loading amount measured based on the first positive electrode active material layer and the second positive electrode active material layer laminated on one side of the current collector, and when positive electrode active material layers are formed on both sides of the current collector, the above range is doubled.

[0109] The positive electrode according to an embodiment of the present invention may have excellent positive electrode adhesion and flexibility even with a small binder content compared to a conventional single-layer positive electrode. As a result, a high-loading positive electrode may be manufactured, and the cell resistance of the secondary battery may be reduced by preventing detachment of the positive electrode, thereby improving the capacity and output characteristics of the battery and reducing defects occurring during the manufacturing process.

[0110] In the positive electrode of the present invention, the adhesive strength between the positive electrode current collector and the positive electrode active material layer, as measured by a 90° peel test, is 22 gf / 20 mm or more, specifically, in the range of 23 gf / 20 mm to 80 gf / 20 mm, and more specifically, 35 gf / 20 mm to 65 gf / 20 mm.

[0111] Furthermore, the positive electrode of the present invention has such flexibility that, during a flexibility test in which a measuring rod of different diameters is brought into contact with the positive electrode active material layer and then the cross section of the positive electrode is lifted, cracks occur with a measuring rod of 5 phi (φ) or less, specifically 4 phi (φ) or less, more specifically 1.5 phi (φ) to 3.5 phi (φ).

[0112] <Lithium secondary battery> Next, the lithium secondary battery according to the present invention will be described.

[0113] A lithium secondary battery according to an embodiment of the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.

[0114] The positive electrode in the lithium secondary battery is as described above. For example, the positive electrode includes a current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer, and the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate, a fluorine-based binder, a rubber-based binder, and a conductive material, and the rubber-based binder includes a first hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol and a second hydrogenated nitrile butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more, and the ratio (P2 / P1) of the weight P1 of the fluorine contained in the first positive electrode active material layer to the weight P2 of the fluorine contained in the second positive electrode active material layer can be 1 or less, preferably 0.5 to 1.

[0115] The positive electrode has been described in detail above, so a duplicated description will be omitted.

[0116] The negative electrode can be manufactured, for example, by preparing a composition for forming a negative electrode, which contains a negative electrode active material, a negative electrode binder, and a negative electrode conductive material, on a negative electrode current collector, and then coating the composition on the negative electrode current collector.

[0117] The negative electrode active material is not particularly limited, and can generally use a compound capable of reversible intercalation and deintercalation of lithium.Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; or a composite containing a metallic compound and a carbonaceous material. In addition, examples of low crystalline carbon include soft carbon and hard carbon, and examples of high crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. Among these, one type alone or a mixture of two or more types may be used, and a metallic lithium thin film may also be used as the negative electrode active material.

[0118] The negative electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one or a mixture of two or more of these may be used. The negative electrode conductive material may usually be contained in an amount of 1% by weight to 30% by weight, specifically 1% by weight to 20% by weight, and more specifically 1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.

[0119] The negative electrode binder plays a role in improving the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The negative electrode binder may be included in an amount of 1% by weight to 30% by weight, specifically 1% by weight to 20% by weight, more specifically 1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.

[0120] Meanwhile, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. may be used.

[0121] The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities on its surface to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0122] Meanwhile, in the lithium secondary battery, the separator can be used without any particular limitation as long as it is one that is generally used as a separator in a lithium secondary battery, and in particular, it is preferable that the separator has low resistance to ion migration of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, etc. can also be used. In addition, the separator can be a porous thin film having a pore diameter of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.

[0123] Meanwhile, in the lithium secondary battery, the electrolyte may contain an organic solvent and a lithium salt that are commonly used in electrolytes, and is not particularly limited.

[0124] The organic solvent may be any organic solvent without particular limitation, so long as it can function as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, examples of the organic solvent that can be used include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; and carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC).

[0125] Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can improve the charge / discharge performance of the battery, and low-viscosity chain carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.

[0126] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0127] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0128] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and then inserting the electrode assembly into a cylindrical or prismatic battery case and then injecting an electrolyte into the battery case. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed.

[0129] When manufacturing the lithium secondary battery of the present invention, the electrode assembly may be dried to remove at least one organic solvent selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate, which was used in manufacturing the positive electrode. When an electrolyte having the same composition as the organic solvent used in manufacturing the positive electrode is used as the electrolyte, the process of drying the electrode assembly may be omitted.

[0130] Unlike the above-described lithium secondary batteries, the lithium secondary battery according to another embodiment of the present invention may be an all-solid-state battery.

[0131] The battery case may be one commonly used in the art, and the shape of the battery case is not limited depending on the intended use of the battery. For example, the battery case may be a cylindrical type using a can, a square type, a pouch type, a coin type, or the like.

[0132] The lithium secondary battery according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, energy storage systems (ESS), and electric vehicles such as hybrid electric vehicles (HEV), etc.

[0133] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples alone.

[0134] <Examples 1 to 6 and Comparative Examples 1 to 5>

[0135] (1) Preparation of Positive Electrode Slurry for the First Positive Electrode Active Material Layer A dispersion liquid was prepared that contained carbon nanotubes (CNTs) as a conductive material and first hydrogenated nitrile butadiene rubber (first HNBR) having a weight average molecular weight (Mw) of 30,000 g / mol as a rubber-based binder.

[0136] Average particle size D as lithium iron phosphate 50 A positive electrode slurry for a first positive electrode active material layer was prepared by adding LiFePO4, which is a primary particle having a single structure with a particle size of 1.0 μm, carbon nanotubes (CNT) as a conductive material, polyvinylidene fluoride (PVDF) having a weight average molecular weight (Mw) of 630,000 g / mol as a fluorine-based binder, second hydrogenated nitrile butadiene rubber (second HNBR) having a weight average molecular weight (Mw) of 310,000 g / mol as a rubber-based binder, and the above dispersion to an N-methylpyrrolidone (NMP) solvent and then mixing at 2500 rpm for 90 minutes using Homo-disperse.

[0137] In each of the positive electrode slurries for the first positive electrode active material layer of Examples 1 to 6 and Comparative Examples 1 to 5, the weight ratios of the lithium iron phosphate, the conductive material, the fluorine-based binder, the first hydrogenated nitrile butadiene rubber, and the second hydrogenated nitrile butadiene rubber were adjusted as shown in Table 1 to prepare the positive electrode slurries for the first positive electrode active material layer.

[0138] (2) Preparation of Positive Electrode Slurry for Second Positive Electrode Active Material Layer Except for changing the weight ratio of the lithium iron phosphate, the conductive material, the fluorine-based binder, the first hydrogenated nitrile butadiene rubber, and the second hydrogenated nitrile butadiene rubber in the positive electrode slurry as shown in Table 1, the positive electrode slurries for the second positive electrode active material layer of each of Examples 1 to 6 and Comparative Examples 1 to 5 were manufactured by the same method as the manufacturing method of the positive electrode slurry for the first positive electrode active material layer.

[0139] (3) Manufacturing of positive electrodes Using a dual slot die coater, 300 mg / 25 cm of the positive electrode slurry for the first positive electrode active material layer was applied onto the aluminum foil. 2 , 300 mg / 25 cm of the positive electrode slurry for the second positive electrode active material layer2 and the positive electrode slurry for the second positive electrode active material layer was coated on the positive electrode slurry for the first positive electrode active material layer.

[0140] Then, the positive electrode slurry was dried with hot air at 130° C. for 5 minutes so that the solid content of the positive electrode slurry was 99.0 wt % or more, and then the dried positive electrode slurry was rolled to prepare a positive electrode so that the porosity of the positive electrode active material layer was 29%.

[0141] [Table 1A] [Table 1B]

[0142] <Experimental Example 1: Measurement of fluorine weight>

[0143] The first and second positive electrode active material layers according to the examples and comparative examples were each scraped to obtain a 100 mg sample, and the weight of fluorine contained in each sample was measured using a combustion reaction technique. The ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer was calculated, and the results are shown in Table 2.

[0144] To measure the weight of fluorine contained in each sample, the first positive active material layer sample and the second positive active material layer sample were completely combusted under high pressure oxygen conditions (40 atm) and the generated gas was collected in an absorbing solution. The gas collection absorbing solution was a 1 L solution containing 2.52 g NaHCO3 and 2.52 g Na2CO3, and when fluorine ions were absorbed or dissolved in the gas collection absorbing solution, the fluorine weight of each sample was measured using ion chromatography. The ion chromatography column and analysis conditions were as follows:

[0145] Ion chromatography: ICS-3000 Column: IonPac AS18 (4 x 250 mm) Detector: suppressed conductivity detector SRS current:76Ma Injection volume: 20uL

[0146] The same test was repeated three times and the average values ​​were shown.

[0147] Based on the results of the ion chromatography analysis, the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer is shown in Table 2.

[0148] <Experimental Example 2: Positive electrode adhesion test>

[0149] The positive electrodes produced in the examples and comparative examples were each vacuum-dried at 130° C. for 2 hours, and then the adhesive strength between each positive electrode active material layer and the positive electrode current collector was measured. The results are shown in Table 2.

[0150] Specifically, the positive electrodes produced in the above examples and comparative examples were cut to a length of 150 mm and a width of 20 mm, and the positive electrode surface was attached to a slide glass with a length of 75 mm and a width of 25 mm in the longitudinal direction using double-sided tape. That is, the slide glass was attached to an area equivalent to half of the longitudinal direction of the positive electrode. Then, a roller was rolled 10 times to uniformly attach the double-sided tape to produce an evaluation sample.

[0151] Next, the glass slide portion of the evaluation sample was fixed to the sample stage of a Universal Testing Machine (UTM) (product name: LS5, manufacturer: LLOYD), and the positive electrode half to which the glass slide was not attached was connected to the load cell of the UTM device. The load cell was moved up to 50 mm at a speed of 100 mm / min, with a 90° force applied, while measuring the load applied to the load cell. At this time, the average value of the load measured in the 20 mm to 40 mm section of the travel section was calculated. This was repeated five times in total, and the average value was evaluated as the positive electrode adhesive strength (gf / 20 mm) of each sample.

[0152] <Experimental Example 3: Positive electrode flexibility test>

[0153] The positive electrodes produced in the above Examples and Comparative Examples were dried in a vacuum at a temperature of 130° C. for 2 hours, and then the flexibility of each positive electrode was measured. The results are shown in Table 2.

[0154] Specifically, the positive electrodes produced in Examples 1 to 6 and Comparative Examples 1 to 5 were cut into 10 cm wide and 30 cm long, and measuring rods with diameters of 2.5φ, 3φ, 4φ, 5φ, 6φ, 7φ, 8φ, 9φ, and 10φ were prepared. Then, the positive electrode collector surface of each cut positive electrode was made to face the measuring rod, and each cut positive electrode was bent in half and both ends of the positive electrode were lifted at a speed of 10 mm per minute. At this time, the positive electrode was lifted until the force measured by UTM reached 5 N. Measurements were made for each diameter, and the electrode was observed with an optical microscope to see if cracks occurred. If no cracks were found, the test was continued with a smaller diameter. The diameter (φ) of the measuring rod at which cracks occurred was shown in Table 2.

[0155] <Experimental Example 4: Viscosity of Positive Electrode Slurry for First Positive Electrode Active Material Layer and Positive Electrode Slurry for Second Positive Electrode Active Material Layer>

[0156] The viscosity of the positive electrode slurry for the first positive electrode active material layer and the viscosity of the positive electrode slurry for the second positive electrode active material layer prepared in each of the above examples and comparative examples were measured. The results are shown in Table 2.

[0157] Specifically, each of the positive electrode slurries for the first positive electrode active material layer and the second positive electrode active material layer was cooled for 1 hour at room temperature and a relative humidity of 1%, and then the viscosity of the positive electrode slurries was measured at 25° C. and a shear rate of 2.5 / s using a viscometer (Brookfield). The viscosity measurement was performed within 2 hours, including the cooling time, after the preparation of the positive electrode slurries for the first positive electrode active material layer and the second positive electrode active material layer.

[0158] [Table 2]

[0159] Referring to Table 2 above, the positive electrode of Comparative Example 1, in which the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer exceeds 1, has inferior adhesion strength compared to the positive electrodes of the Examples.

[0160] The positive electrode according to Comparative Example 2 does not contain the second hydrogenated nitrile butadiene rubber, and therefore is inferior in flexibility to the positive electrodes according to the Examples.

[0161] In the positive electrode of Comparative Example 3, the positive electrode slurry for the first positive electrode active material layer and the positive electrode slurry for the second positive electrode active material layer did not contain the first hydrogenated nitrile butadiene rubber, and therefore the lithium iron phosphate and the conductive material contained in the slurries were severely coagulated, making it impossible to manufacture the positive electrode using a dual slot die coater.

[0162] In the positive electrode of Comparative Example 4, the viscosity of the positive electrode slurry for the second positive electrode active material layer was too high, which reduced the coating performance and made it impossible to manufacture the positive electrode using a dual slot die coater. In the positive electrode of Comparative Example 5, the viscosity of the positive electrode slurry for the first positive electrode active material layer was too high, making it impossible to manufacture the positive electrode.

[0163] As described above, the positive electrode according to the present invention includes a first positive electrode active material layer and a second positive electrode active material layer. The first positive electrode active material layer and the second positive electrode active material layer each include a fluorine-based binder, a first hydrogenated nitrile butadiene rubber, a second hydrogenated nitrile butadiene rubber, and a conductive material in a predetermined weight ratio, and thus have a capacitance of 550 mg / 25 cm. 2 ~750mg / 25cm 2 As a result, a high-loading positive electrode can be manufactured, and the cell resistance of the secondary battery can be reduced by preventing the positive electrode from being detached, thereby improving the capacity and output characteristics of the battery and reducing defects that occur during the manufacturing process.

Claims

1. A positive electrode including a current collector, a first positive electrode active material layer formed on the current collector, and a second positive electrode active material layer formed on the first positive electrode active material layer, the first positive electrode active material layer and the second positive electrode active material layer each contain lithium iron phosphate, a fluorine-based binder, a rubber-based binder, and a conductive material; The rubber-based binder includes a first hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 10,000 g / mol to 100,000 g / mol, and a second hydrogenated nitrile-butadiene rubber having a weight average molecular weight (Mw) of 130,000 g / mol or more, A positive electrode, wherein a ratio (P2 / P1) of a weight P2 of fluorine contained in the second positive electrode active material layer to a weight P1 of fluorine contained in the first positive electrode active material layer is 1 or less.

2. 2. The positive electrode according to claim 1, wherein a ratio (P2 / P1) of a weight P2 of fluorine contained in the second positive electrode active material layer to a weight P1 of fluorine contained in the first positive electrode active material layer is 0.5 to 1.

3. 2. The positive electrode of claim 1, wherein the first positive electrode active material layer comprises 0.9 wt % or less of the second hydrogenated nitrile butadiene rubber based on the weight of the first positive electrode active material layer.

4. a weight ratio of the fluorine-based binder to the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer is 90:10 to 75:25; 2. The positive electrode of claim 1, wherein a weight ratio of the fluorine-based binder to the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer is 80:20 to 60:

40.

5. The first positive electrode active material layer has a weight ratio of, based on the weight of the first positive electrode active material layer, 93.5% by weight to 97.99% by weight of the lithium iron phosphate, The fluorine-based binder is 1.5% by weight to 3.0% by weight, 0.01% by weight to 0.7% by weight of the first hydrogenated nitrile butadiene rubber, 0.2% by weight to 0.8% by weight of the second hydrogenated nitrile butadiene rubber, 2. The positive electrode of claim 1, comprising 0.3% to 2.0% by weight of the conductive material.

6. The second positive electrode active material layer has a weight ratio of, based on the weight of the second positive electrode active material layer, 94.2% by weight to 98.49% by weight of the lithium iron phosphate; The fluorine-based binder is 0.9% by weight to 2.2% by weight, 0.01% by weight to 0.7% by weight of the first hydrogenated nitrile butadiene rubber, 0.3% to 0.9% by weight of the second hydrogenated nitrile butadiene rubber, 2. The positive electrode of claim 1, comprising 0.3% to 2.0% by weight of the conductive material.

7. 2. The positive electrode of claim 1, wherein the weight average molecular weight (Mw) of the second hydrogenated nitrile butadiene rubber is 150,000 g / mol to 1,000,000 g / mol.

8. 2. The positive electrode according to claim 1, wherein the fluorine-based binder contained in the first positive electrode active material layer and the fluorine-based binder contained in the second positive electrode active material layer are the same compound.

9. 2. The positive electrode according to claim 1, wherein a ratio (=H2 / H1) of the weight % (H2) of the second hydrogenated nitrile butadiene rubber contained in the second positive electrode active material layer to the weight % (H1) of the second hydrogenated nitrile butadiene rubber contained in the first positive electrode active material layer is 1 to 3.

10. The positive electrode according to claim 1, wherein the lithium iron phosphate is a compound represented by the following chemical formula 1: [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b (In the above Chemical Formula 1, M includes one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; X includes one or more elements selected from the group consisting of F, S, and N; and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively).

11. The positive electrode of claim 1 , wherein the conductive material is a carbon nanotube.

12. 2. The positive electrode according to claim 1, wherein a ratio (C2 / C1) of the weight percentage C2 of the conductive material contained in the second positive electrode active material layer to the weight percentage C1 of the conductive material contained in the first positive electrode active material layer is 0.5 to 2.

13. The total loading amount of the first positive electrode active material layer and the second positive electrode active material layer is 400 mg / 25 cm 2 ~700mg / 25cm 2 The positive electrode of claim 1 , wherein the ionic liquid is in the range of

14. 2. The positive electrode according to claim 1, wherein the positive electrode adhesive strength measured in an adhesive strength test in which the first positive electrode active material layer is peeled off from an aluminum thin film at an angle of 90° is 22 gf / 20 mm or more.

15. The positive electrode according to claim 1 , wherein a crack occurs with a measuring rod of 5 phi (φ) or less during a flexibility test in which a cross section of the positive electrode is lifted after contacting the positive electrode active material layer with the measuring rod.

16. A lithium secondary battery comprising the positive electrode according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Lithium secondary battery and manufacturing method thereof

    JP2005123047A

  • Positive electrode for lithium secondary battery and lithium secondary battery equipped therewith

    JP2012531726A

  • Positive electrode mixture and secondary battery containing the same

    JP2018523281A

  • Conductive material paste composition for secondary battery electrodes, slurry composition for secondary battery electrodes, undercoat layer-including current collector for secondary battery electrodes, electrode for secondary batteries, and secondary battery

    WO2017056488A1

  • Electrode and manufacturing method therefor

    WO2022191645A1